1996
DOI: 10.1002/(sici)1099-1573(199606)10:4<292::aid-ptr834>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Trypanocidal Sesquiterpenes fromLychnophora Species

Abstract: The bioguided fractionation of the crude extracts of Lychnophora passerina (Mart. ex DC) Gardn., L. pinaster Mart. and L. trichocarpha Spreng. led to the isolation of four compounds active against the trypomastigote forms of Trypanosoma cruzi: the sesquiterpene lactones goyazensolide (1), eremantholide C (2), and lychnopholide (3) and a new caryophyllene derivative, which was named lychnophoic acid (4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
10

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 6 publications
2
50
0
10
Order By: Relevance
“…5 Compounds 5 and 6 were isolated from aerial parts of Lychnophora trichocarpha. 7 Physical data of these lactones, including optical rotation, were consistent with published data.…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…5 Compounds 5 and 6 were isolated from aerial parts of Lychnophora trichocarpha. 7 Physical data of these lactones, including optical rotation, were consistent with published data.…”
Section: Methodssupporting
confidence: 85%
“…Incubation of 1 with C. echinulata afforded ∆ 11 (13) dihydrogenation and ∆ 1(10) -epoxidation products (7)(8)(9)(10). C. echinulata also hydrolyzed the side chain of 2, and transformed 4 into (+)-11R,13-dihydrodehydrocostuslactone (12), a new natural product.…”
mentioning
confidence: 99%
“…The sesquiterpene lactones of the furanheliangolide type are biogenetically derived from heliangolides and are often found in species of the genus Lychnophora, that is native from Brazil (Bohlmann and Jakupovic 1990). In previous studies, eremantholide C and its oxidized derivatives showed activity against Trypanosoma cruzi (Oliveira et al 1996, Saúde-Guimarães et al 2007). Other biological/pharmacological activities were reported for eremantholide C, such as antibacterial, anti-hyperuricemic, anti-gouty arthritis, anti-inflammatory and antitumor (Barrero et al 2000, Saúde et al 2002, de Souza et al 2012, DÊNIA A. SAÚDE-GUIMARÃES, DÉLIO S. RASLAN, EGLER CHIARI and ALAÍDE B.…”
Section: Introductionmentioning
confidence: 98%
“…In previous work, a phytochemical study of the hexane and ethanol extracts from the aerial parts of L. pinaster led to isolation of the E-isomer of lychnophoric acid (named lychnophoic acid), quercetin, 15-deoxygoyazensolide, lupeol, a mixture of α-and β-amyrin, friedelin and fat acid esters mixture Silveira et al, 2005) and saturated hydrocarbons . Lychnophora pinaster hexane and ethanol extracts and isolated E-isomer of lychnophoric acid showed in vitro trypanocidal activity against trypomastigote forms of T. cruzi (Silveira et al, 1993;Oliveira et al, 1996). In a continuing effort to known more about this species, assays were carried out to detect biological activity of the aqueous extract from aerial parts of L. pinaster.…”
Section: Introductionmentioning
confidence: 99%